PENGARUH MATA PELAJARAN KEWIRAUSAHAAN, STATUS SOSIAL EKONOMI ORANG TUA, DAN INTERNAL LOCUS OF CONTROL TERHADAP MINAT BERWIRAUSAHA SISWA KELAS XI TKJ SMK BATIK 1 SURAKARTA TAHUN AJARAN 2017/2018 - -, Amalia Shofiy Suci Utami -; -, Bambang Wasito Adi -; -, Sunarto - (Jurnal Pendidikan Bisnis dan Ekonomi, 2018)
The objectives of the research are to know (1) the impact of entrepreneurship subject parents? social-economic status and internal locus of control toward the entrepreneurship interest of second grade students of TKJ program (2) the impact of entrepreneurship subject toward the entrepreneurship interest of second grade students of TKJ program (3) the impact of parents? social-economic status toward the entrepreneurship interest of second grade students of TKJ program (4) the impact of internal locus of control toward the entrepreneurship interest of second grade students of TKJ programDescriptive qualitative method is used in this research in the form of expost-facto research. Technique used to collect the data is questionnaire in the form of 46 items which has been tested it's validity. Simple of the research is jenuh sampling or sampling the whole of population 2nd grade students of TKJ programme which is 90 studentsBased on the finding it can be concluded that : (1) there is a significant impact among entrepreneurship subject, parents? social-economic status and internal locus of control toward the entrepreneurship interest of second grade students of TKJ program of SMK Batik 1 Surakarta Academic year 2017/2018. It proven from Fcount>Ftable (35,188>2,711).  (2) there is a positive significant impact of entrepreneurship subject toward entrepreneurship interest of second grade students of TKJ program of SMK Batik 1 Surakarta Academic year 2017/2108, it can be seen from tcount>ttable(4,572>1,988).  (3) there is a negative significant impact on parents? social-economic status toward entrepreneurship interest of second grade students of TKJ program of SMK Batik 1 Surakarta Academic year 2017/2108, it can be seen from tcount>ttable(-2,016>-1,988). (4) there is a positive significant impact on internal locus of control toward entrepreneurship interest of second grade students of TKJ program of SMK Batik 1 Surakarta Academic year 2017/2108, it can be seen from tcount>ttable(7,395>1,980).